(Re)Centralisation of education governance in Hungary: its causes, declared goals, motives and some potential hidden goals - András Semjén (Jan Dlugosz University, 2023)
After municipalities (local governments) and county level governments were established in Hungary in 1990, public education was operated, governed and financed by these elected bodies with the financial support of the central government until the end of 2012. In this decentralised system differences in local wealth and income of municipalities led to significant inequalities in the funding and performance of their schools, and the learning outcomes of the children studying in these. The FIDESZ-KDNP coalition government that took office in 2010 radically centralised the system of governance and funding of schools, claiming that this will be a remedy to the problems of the system. Based on a large set of research interviews and previous research results our paper investigates the declared goals of this reform, and tries to explore its motives as well. According to our research interviews granting equal opportunity in education to every child seems to be the overarching goal of centralisation, and there are three more other goals as well, including the creation of a more efficient and cost-effective system of institutional management. However, some characteristics of the selection of these goals and the seemingly complete lack of the monitoring of their fulfilment, together with the fact that independent research already proved that the centralisation was definitely unable to achieve its main declared goal, may substantiate the claim that this just served as a cover or pretext, and there probably exists a hidden agenda that is more important for the government than the publicly declared goals. Based on interviews with former politicians, education researchers, advisors and school headmasters we tried to find some of the possible real motives and hidden goals. Although the existence of such goals is impossible to prove exactly, we found several circumstances that may substantiate their existence.